Energy efficient solutions for electrodes pitch diameter of electric arc furnace (Modern Problems of Metallurgy, 2019)
Analysis of recent research and publications. Modern mathematical models of the scrap heating and melting process in the EAF do not reflect the influence of the electrodes pitch diameter value relative to the diameter of the furnace frame on the EAF energy efficiency. Traditional ratio is based on the task of minimization arcs irradiation on the EAF walls refractory lining, which is not actual in modern units with wide using of water cooled panels.Purpose. To increase the EAF energy efficiency by optimization of .Methodology. Numerical simulations of the arc furnace scrap heating and melting process due to radiation heat exchange, when varying the ratio, is the subject scope of the paper.Findings. Energy-efficient solutions for in different capacity EAF, operating by intensive technology with standard bucket charging.Research implications: Calculation of partial arcs energy efficiency ratios in the individual wells and overall well, which are melted in the charge, shows these values are 0.94 and 0.70 correspondingly. Has been revealed the influence of on the relative duration of closed and open arcing and, thus, on the total duration of melting period , most energy-intensive in the EAF steelmaking modern technology, as a whole. According to research, in the EAF with an optimal value of ratio, increases by 16%, decreases by 15% and decreases by 4%, relative to traditional ratio.Practical implications. Increasing of the ratio from traditional 0.2 to (0.42−0.49) improves the energy efficiency of the EAF by changing of the melting mode and leads to energy savings of 5–6% in large furnaces (120–250 tons) and 2–3% in small capacity ones (12–15 tons). The optimal value of grows from 0.42 to 0.49 with an increase in the EAF capacity from 15 to 250 tons.Originality. The new concepts of the EAF energy saving working space geometry, based on thermal and technological features of given unit.
Keywords: electric arc steel-smelting furnace; heat exchange; electrodes pitch diameter; energy efficiency